Pemberdayaan Masyarakat Melalui Edukasi Business Model Canvas (BMC) Di SMK Negeri 1 Ketungau Hilir Provinsi Kalimantan Barat - Mhd. Hamdika Ersyah Lubis; Viki Ardiansyah Rambe; Yosua Benardo Simangunsong; Ivan Rionaldo Damanik; Ismiasih (Politeknik Piksi Ganesha Indonesia, 2026)
There is a need to increase the capacity and readiness of vocational high school students to develop local potential creatively and sustainably through strengthening entrepreneurial insight and utilizing digital media. The goal of empowerment is to improve understanding, skills, and integration of competencies between departments in managing and promoting products derived from local potential. The methods used include outreach, training, and applied practice with a participatory and contextual approach. The results of the community service show an increase in students' knowledge, creativity, and ability to develop business ideas and utilize digital media as a promotional tool, thus positively impacting students' readiness to become entrepreneurs and contribute to the development of the surrounding community.